Vitamin C and Vitamin E Mitigate the Risk of Pancreatic Ductal Adenocarcinoma from Meat-Derived Mutagen Exposure in Adults in a Case-Control Study. Issue 8 (17th May 2019) - Li, Donghui; Tang, Hongwei; Wei, Peng; Zheng, Jiali; Daniel, Carrie R; Hassan, Manal M
ABSTRACT: Background: Previous studies have found that meat-derived mutagens increase, and vitamin C or E decrease, the risk of pancreatic cancer. Objective: The aim of this study was to determine whether intake of vitamin C or E modulates the association between meat-derived mutagen exposure and risk of pancreatic cancer. Design: We conducted a case-control study in 1321 patients with pathologically confirmed pancreatic ductal adenocarcinoma (PDAC) and 1061 healthy controls (aged 28–88 y). Cases and controls were frequency-matched by age, sex, and race/ethnicity. Mutagen intake was assessed using a meat preparation questionnaire. Intakes of vitamin C, E, and other dietary components were assessed via a food-frequency questionnaire in a subset of 811 cases and 818 controls. ORs and 95% CIs were estimated in multivariable-adjusted logistic regression models. Results: The risk of PDAC was not associated with meat intake but was associated with consumption of well-done grilled or barbecued chicken (OR: 1.57; 95% CI: 1.18, 2.09; P = 0.001). Intake of 2-amino-3, 8-dimethylimidazo[4, 5-f]quinoxaline was associated with increased PDAC risk ( P trend = 0.047). Participants in the highest, as compared with the lowest, quintile of 2-amino-3, 4, 8-trimethylimidazo[4, 5-f]quinoxaline (PhIP) intake experienced a 38% increased risk of PDAC (95% CI: 1.00, 1.90; P = 0.048). Intakes of total vitamin C or E from food and supplements or from supplements alone were each inversely associated with PDAC risk. Stratified analyses showed differential associations for PhIP intake and PDAC risk, such that risk increased among individuals with lower intake of vitamin C or E and decreased among those with higher vitamin intake. Significant interactions of dietary vitamin C, dietary vitamin E, and total vitamin E with PhIP intake were detected ( P interaction = 0.023, <0.001, and 0.013, respectively). Conclusions: Consistent with experimental evidence, this study of 811 cases and 818 controls has shown that high intake of dietary vitamin C or E mitigates the risk of PhIP-related PDAC.